Production and fermentation characteristics of angiotensin-I-converting enzyme inhibitory peptides of goat milk fermented by a novel wild Lactobacillus plantarum 69 - Chen, Li; Zhang, Qiuhong; Ji, Zhe; Shu, Guowei; Chen, He (Food science & technology, 2018)
Food derived angiotensin-I-converting enzyme (ACE)-inhibitory peptides are normally from products fermented by Lactobacillus helveticus but seldom by other lactic acid bacteria. In this study, a novel wild strain L. plantarum 69 was identified genetically and applied to ferment goat milk with high ACE-inhibitory activity, flourished bacterial population, and ideal flavor. The fermentation condition was optimized with the aid of response surface methodology (RSM). The optimal fermentation condition were temperature of 35 °C, CaCl2 concentration of 0.07%, and Tween-80 concentration of 0.04%. The ACE-inhibitory activity of the fermented product reach 88.91% which was approximately close to the predicted 91.68%. Purification was operated by ultrafiltration, macroporous resin DA201-C, gel chromatography, and reverse-phase high performance liquid chromatography (RP-HPLC), and finally exhibited the ACE-inhibitory activity of 91.62%. Goat milk fermented by L69 successfully survived in gastrointestinal tract and maintained high ACE-inhibitory activity. •Goat milk fermented by L. plantarum 69 showed great characteristic.•The optimal fermentation was temperature of 35 °C, CaCl2 of 0.07% (w/v), and Tween-80 of 0.04% (v/v).•The purified fermentation product exhibited high ACE-inhibitory activity.•Fermentation product survived in gastrointestinal tract with high ACE-inhibitory activity.